PERCEPTION AND ATTITUDE TOWARD THE DEVELOPMENT OF HALAL TOURISM IN BANGKA DISTRICT INDONESIA - Wulpiah Wulpiah; Aam Slamet Rusydiana (Univeristas Islam Bandung, 2022)
Tourism is one sector that has an important role in regional economic development. But unfortunately, the development of tourism, especially halal tourism in Indonesia, is still a polemic among the public. The purpose of this study was to analyze and describe the perceptions and attitudes of the people of Bangka District towards Halal Tourism Development. This type of research is a survey with a quantitative approach with a total sample of 263 respondents. The data collection technique used Cluster Random Sampling. The method used is Multiple Linear Regression Analysis with Statistical Package for Social Sciences (SPSS) 22 software. The results of this study indicate that public perceptions and attitudes significantly influence the development of halal tourism in Bangka District. It can be seen from the calculated F value > F table (386.397 > 3.031) with a significance of 0.000 <0.05 and partially each independent variable affects the dependent variable, namely the development of halal tourism. The magnitude of the influence seen from the value of the coefficient of determination is 74.8% and the remaining 25.2% is influenced by other variables not examined. So this model is very suitable for developing halal tourism.